2014
DOI: 10.2989/17280583.2014.947966
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, parenting styles and bullying during pubertal years

Abstract: Research that focuses on combining attachment, parenting styles, bullying and the reciprocal nature thereof in the parent-adolescent and peer relationships is limited. The bio-psychosocial changes that adolescents experience open up broader social realities and are perceived differently by parents and adolescents. Attachment processes and parenting styles may elicit dissimilar perceptions. These processes are also associated with the multifaceted dynamics of bullying. The aim of the article is to advocate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Other studies have also demonstrated an association between parenting style and being bullied [ 10 , 32 ], and parental overcontrol has been found to be a risk factor for bullying among adolescent girls. The mechanism could be that parental overcontrol and protection limits adolescents’ opportunities to interact with certain kinds of peers and prevents adolescents from developing a diverse set of social skills [ 70 ]. Another mechanism could be that children, through their experiences at home (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated an association between parenting style and being bullied [ 10 , 32 ], and parental overcontrol has been found to be a risk factor for bullying among adolescent girls. The mechanism could be that parental overcontrol and protection limits adolescents’ opportunities to interact with certain kinds of peers and prevents adolescents from developing a diverse set of social skills [ 70 ]. Another mechanism could be that children, through their experiences at home (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in European or Latin American countries support the indulgent parental style as beneficial (García & Gracia, 2009, 2014Martínez et al, 2013). These authors argue that any nonpositive behavior has a detrimental effect, and only affection based on acceptance, support, and reasoned communication promote appropriate behavior.…”
Section: Parenting Styles and Dimensions In The Development Of Externalizing Behaviorsmentioning
confidence: 99%
“…Studies that explore the influence of different parenting styles and the development of externalizing behaviors found that the authoritative style is the only one that provides clear positive effects in a child's adaptation, promoting resilience, self-esteem, and a better psychological adjustment. In contrast, the other styles (authoritarian, indulgent, or negligent) place a child at risk of suffering externalization problems (Luk, Patock-Peckham, Medina, Belton, & King, 2016;Mestre, Tur, Samper, & Latorre, 2010;Oliva, Parra, & Arranz, 2008;Tur-Porcar, Mestre, Samper, & Malonda, 2012;van der Watt, 2014).…”
mentioning
confidence: 99%
“…This relationship is linked to the parenting style (Van der Watt, 2014). A supportive parenting style reduces victimisation and perpetration for SB (Aslan, 2011;Rajendran, Kruszewski & Halperin, 2016).…”
Section: Family and Friendsmentioning
confidence: 99%